2002
DOI: 10.1007/s00221-001-0947-y
|View full text |Cite
|
Sign up to set email alerts
|

Areas of the human brain activated by ambient visual motion, indicating three kinds of self-movement

Abstract: In a positron emission tomography (PET) study, a very large visual display was used to simulate continuous observer roll, yaw, and linear movement in depth. A global analysis based on all three experiments identified brain areas that responded to the three conditions' shared characteristic of coherent, wide-field motion versus incoherent motion. Several areas were identified, in the posterior-inferior temporal cortex (Brodmann area 37), paralimbic cortex, pulvinar, and midbrain tegmentum. In addition, occipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 17 publications
3
40
0
Order By: Relevance
“…The coherent stimulus induced compelling vection. In a subsequent PET study, Beer et al [2002] compared large-field coherent visual motion stimuli, which simulated three different kinds of observer movement (roll, yaw, and linear movement in depth), to three corresponding incoherent visual motion stimuli, which were designed to induce weaker vection in the same planes and directions. Brain areas in the left temporal lobe (BA 37), the pulvinar, amygdala, anterior cingulate gyrus, midbrain tegmentum, and KO were interpreted to respond specifically to the coherence of the stimuli.…”
Section: Neural Substrates For Mediation Of Vection and Coherent Motimentioning
confidence: 99%
See 2 more Smart Citations
“…The coherent stimulus induced compelling vection. In a subsequent PET study, Beer et al [2002] compared large-field coherent visual motion stimuli, which simulated three different kinds of observer movement (roll, yaw, and linear movement in depth), to three corresponding incoherent visual motion stimuli, which were designed to induce weaker vection in the same planes and directions. Brain areas in the left temporal lobe (BA 37), the pulvinar, amygdala, anterior cingulate gyrus, midbrain tegmentum, and KO were interpreted to respond specifically to the coherence of the stimuli.…”
Section: Neural Substrates For Mediation Of Vection and Coherent Motimentioning
confidence: 99%
“…Beer et al [2002] compared visually induced vection in roll, yaw, and linear movement in depth and found responses in a posterior-inferior temporal area, in the paralimbic cortex, pulvinar, midbrain tegmentum, and in the kinetic occipital region (KO), an area located on the occipital pole approximately 20 mm behind MT/V5, which is involved in the processing of kinetic borders [Dupont et al, 1997]. In the study by Beer et al [2002], a region in the right insula appeared to respond specifically to roll motion. Sites apparently selective for linear movement in depth were identified in the right cerebellum and in both temporal lobes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The regions of interest in this case study are shown to be active in tasks regarding social cognition, interpreting the mental states of others, emotion, memory, learning, decision making, reward, motivation and self reference, encoding, reality monitoring, suicide, empathetic and addictive processes (Abrahams et al, 2003;Adinoff, 2004;Alberto Tassinari et al 2005;Bechara & Damasio, 2002;Beer, Blakemore, Previc, & Liotti, 2002;Berthoz, Armony, Blair, & Dolan, 2002;Buss, Wolf, Witt, & Hellhammer, 2004;Cannon, Lubar, Thornton, Wilson, & Congedo, 2004;Critchley, 2005;du Boisgueheneuc et al, 2006;Fleck, Daselaar, Dobbins, & Cabeza, 2006;Fossati et al, 2003;Goel, Grafman, Sadato, & Hallett, 1995;Goldstein et al, 2007;Grady & Keightley, 2002;Gusnard, 2005;Gusnard, Akbudak, Shulman, & Raichle, 2001;Heiser, Iacoboni, Maeda, Marcus, & Mazziotta, 2003;McNaughton et al, 1996;Stellar & Corbett, 1989;Walton, Croxson, Behrens, Kennerley, & Rushworth, 2007). One important concept regarding alpha activity in limbic regions as estimated by sLORETA and its relationship to SUD may be that these particular frequencies maintain a state of desynchronization within the individual, which in turn affects autonomic functioning, perceptual and cognitive processes, and numerous other personality and psychological factors.…”
Section: Discussionmentioning
confidence: 88%
“…The perceived relative motion is important for posture control [20]. Taking advantage of improved brain imaging techniques, a better understanding of the visual motion and self-movement interactions has been pursued [21], [22]. A Bayesian model of human processing of vestibular information is proposed by [23], obtaining satisfactory responses to complex motion stimuli.…”
Section: A Related Workmentioning
confidence: 99%